(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The analysis of clinical observations in the dialysis intensive care unit has shown that concomitant liver damage often aggravates the course of OPP, leading in some cases to an unfavourable outcome. This prompted us to investigate the functional state of the liver in patients with OPP in the oligoanuria stage depending on the severity of azotemia at their admission to the intensive care unit for the purpose of early diagnosis of the nature and severity of liver damage, timely targeted therapy and the possibility of predicting this combination.